Better late than never - Kaye, Marilyn (Kingfisher, 2009)
Jenna Kelley has always dreamed of living a conventional life with normal parents, despite her supernatural gifts, but when her mother winds up in rehab and her estranged father unexpectedly shows up, she knows there is no chance of her dream coming true, especially when she uncovers her father's dark secret.